A growth reference for mid upper arm circumference for age among school age children and adolescents, and validation for mortality: growth curve construction and longitudinal cohort study - Mramba, L; Ngari, M; Mwangome, M; Muchai, L; Bauni, E; Walker, A; Gibb, D; Fegan, G; Berkley, J (BMJ Publishing Group, 2017)
Objectives Worldwide, school age children and adolescents are vulnerable to conflict and food insecurity and HIV-infected children are increasingly surviving into adolescence. WHO recommends assessing acute malnutrition in this age group using body mass index-for-age Z scores (BMIz). For under-fives, mid upper arm circumference (MUAC) is the mainstay of community diagnosis of acute malnutrition, is simple to perform and predicts survival better than weight-for-height Z scores. MUAC is little-used in older children and adolescents because there is no accepted international reference. This study aimed to construct growth curves for MUAC-for-age Z score (MUACz) for 5-19 year olds that accord with WHO Growth Standards, and evaluate their discriminatory performance for subsequent mortality. Design The HES/NHANES US population datasets (age 5-25 years), which were used to construct the 2007 WHO Growth Reference for BMI in this age group, were merged with an imputed dataset matching the distribution of the WHO 2006 Growth Standards age 2-6 years. To construct standardised growth curves, we used Generalized Additive Models for Location, Scale and Shape with Box-Cox Cole Green transformation and penalized B-spline smoothing. Validation for subsequent mortality in two cohorts was done using Cox proportional hazards models for pre-defined MUACz and BMIz thresholds, with age, gender and HIV status as covariates; and estimation of the area under receiver-operating characteristic curves (AUC). Participants Validation data were from 685 HIV-infected children age 5¬–17 years participating in the ARROW trial in Uganda and Zimbabwe; and 1,741 children age 5–13 years discharged from a rural Kenyan hospital (3.8% HIV-infected). Both cohorts were followed up for survival during one year. Main outcome measures Concordance with WHO 2006 Growth Standards at age 60 months and survival during one year according to MUACz and BMIz. Results The new growth curves transitioned smoothly with WHO Growth Standards at age 5 years. MUACz of -2 to -3 and <-3, compared with ≥-2, was associated with hazard ratios for death within one year of 3.63 (95%CI 0.90 to 14.7; P=0.07) and 11.1 (95%CI 3.40 to 36.0; P<0.0001) respectively among ARROW trial participants; and 2.22 (95%CI 1.01 to 4.9; P=0.04) and 5.15 (95%CI 2.49 to 10.7; P<0.0001) respectively among Kenyan children after discharge from hospital. The AUCs for MUACz and BMIz for discriminating subsequent mortality were 0.81 (95%CI 0.70 to 0.92) and 0.75 (95%CI 0.63 to 0.86) in the ARROW trial (absolute difference 0.06 (95% CI -0.032 to 0.16; P=0.2); and 0.73 (95%CI 0.65 to 0.80) and 0.58 (95% CI 0.49 to 0.67) respectively in Kenya (absolute difference in AUC 0.15 (95% CI 0.07 to 0.23; P=0.0002). Conclusions MUACz is at least as effective as BMIz for assessing mortality risks associated with undernutrition among African school-aged children and adolescents. MUAC can provide simplified screening and diagnosis within nutrition and HIV programmes, and in research.